Dizu Zungula Mzikantu Plaatjies: Converging worlds of African Music at the University of Cape Town, 1992-2024 - Grayer, Fiona Marian (Stellenbosch : Stellenbosch University, 2026)
Thesis (MMus)--Stellenbosch University, 2026.